Integration of Local Culture into Communicative Language Teaching Method to Improve Speaking Ability of Extracurricular Students of SMPN 15 Bekasi - Rohman, Fadlur; Deprina, Faza Putri; Silalahi, Rachel Martha Ully; Wirianti, Zubaidah; Manurung, Ersa Beta Damayanti; Widya, Widya (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The Community Service Program (PKM-PM) at SMPN 15 Bekasi City, which ran from 30 April to 18 July 2024, aimed to improve students' speaking skills through wayang performances in English. By applying the Communicative Language Teaching (CLT) method, the program combined the structural and functional aspects of language with local culture through shadow puppets and folklore in seven meetings that included material explanation, demonstration of puppet movements, and role play. The evaluation showed students' enthusiasm and significant progress in speaking skills, with 15 students successfully performing a wayang performance in English with improved vocabulary, confidence and speaking skills. To ensure the sustainability of the program, regular training for teachers, integration of the program in the extracurricular curriculum, development of a puppet-based learning module, involvement of alumni and parents, and periodic evaluations to measure effectiveness are recommended. In addition, seeking collaborations with other educational institutions, cultural organizations, and providing additional resources such as books and online materials will support the future success of the program.